Peramalan Nilai Tukar Petani Kabupaten Lamongan dengan Arima - Mohammad Syaiful Pradana; Dinita Rahmalia; Ericha Dwi Ayu Prahastini (Jurnal Matematika, 2020)
Agriculture is a sector that has a significant role for the Indonesian economy. In Lamongan Regency, about 35.71 percent of the workers depends on the primary agricultural sector, so it is not surprising that the agricultural sector is the basis of growth, especially in rural areas. Agricultural development is oriented towards improving the welfare of farmers. One of the measurements the level of farmer welfare is by calculating the Farmer Exchange Rate. It is the relationship between the produce sold by farmers and the goods and services purchased by farmers. Seeing how important this Farmer Exchange Rate is, predicting the value of Farmer Exchange Rate in the following year will be very useful. The results of this value can be a benchmark to anticipate all situations in the following years and how to control the rising value of Farmer Exchange Rate so as to improve the welfare of the people of Lamongan. From the results of the analysis and discussion, food plants have a low NTP value, namely ?100 per month for a period of 3 years and have the highest Farmer Exchange Rate reduction in 2019 of 10.25%.